Building resilient food systems: integrating ontologies in Sejahtera-Souq for IIUM's sustainable marketplace - Hassan, Mohd Khairul Azmi; Amir Hussin, Amir 'Aatieff; Muhamad Ibrahim, Najhan; Mokhtar, Rahmah; Ahmad Uzir, Nora'ayu; Mat Nayan, Norshita (Global Academic Excellence, 2025)
Sustainable food systems are integral to addressing global challenges such as food security, environmental degradation, and socio-economic resilience. As the demand for sustainable practices grows, ontologies provide a powerful means to organize, manage, and analyze the complexity of these systems. This paper examines the integration of ontologies into the Sejahtera-Souq, a marketplace initiative at the International Islamic University Malaysia (IIUM), to bolster food system resilience. Ontologies allow for a structured representation of data across the food supply chain, enabling automated sustainability assessments, greater transparency, and more efficient operations. Sejahtera-Souq, in line with IIUM’s sustainability goals, stands to benefit significantly from ontology-based tools. By adopting such frameworks, the marketplace can track and manage food and optimize resource use. Moreover, ontologies can aid in mapping relationships between food products, their origins, processing methods, and their environmental impacts. This will facilitate informed decision-making for both producers and consumers, promoting a culture of sustainability on campus. This study not only reviews current applications of ontologies in food systems but also proposes a roadmap for integrating these technologies into Sejahtera-Souq. Through the use of ontology-driven intelligence, the marketplace can align itself with international standards for sustainability while fostering local socio-economic growth. The incorporation of these technologies into Sejahtera-Souq can serve as a model for other institutions seeking to implement sustainable marketplace frameworks, demonstrating how academic institutions can play a leading role in the global shift towards more resilient food systems.